Studi Deskriptif Tingkat Literasi Pasar Modal: (Pada Mahasiswa Fakultas Ekonomi dan Bisnis Program Studi Akuntansi UNDANA Kupang) - Filipus Argentano Guntur Suryaputra (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
The Capital Market is an object that must be known by students of economics, especially in the area of specialization in the concentration of financial accounting. Knowledge of the capital market will be beneficial for students so that they are able to engage and apply it in securities trading activities. This study aims to describe and identify the extent to which the level of knowledge of students, especially in the field of accounting in financial concentration, in observing phenomena that occur in the Indonesian capital market. There is a research location in Kupang City, Nusa Cendana University Accounting Study Program (UNDANA). The research implementation lasted 6 months. The overall level of Capital Market literacy is still low related to capital market knowledge in accounting students with a concentration in finance. It is necessary to cultivate an intention to study the capital market and the importance of the level of capital market literacy in students.